Few Plasmodium falciparum merozoite ligand and erythrocyte receptor pairs show evidence of balancing selection - Ochola-Oyier, L; Wamae, K; Omedo, I; Ogola, C; Matharu, A; Musabyimana, J; Njogu, F; Marsh, K (Elsevier, 2019)
Erythrocyte surface proteins have been identified as receptors of Plasmodium falciparum merozoite proteins. The ligand-receptor interactions enable the parasite to invade human erythrocytes, initiating the clinical symptoms of malaria. These interactions are likely to have had an evolutionary impact on the genes that encode the ligand and receptor proteins. We used sequence data from Kilifi, Kenya to detect departures from neutrality in a paired analysis of P. falciparum merozoite ligands and their erythrocyte receptor genes from the same population. We genotyped parasite and human DNA obtained from 93 individuals with severe malaria. We examined six merozoite ligands EBA175, EBL1, EBA140, MSP1, Rh4 and Rh5, and their corresponding erythrocyte receptors, glycophorin (Gyp) A, GypB, GypC, band 3, complement receptor (CR) 1 and basigin, focusing on the regions involved in the ligand-receptor interactions. Positive Tajima's D values (>1) were observed only in the MSP1 C-terminal region and EBA175 region II, while negative values (<-1) were observed in EBL-1 region II, Rh4, basigin exons 3 and 5, CR1 exon 5, Gyp B exons 2, 3 and 4 and Gyp C exon 2. Additionally, ebl-1 region II and basigin exon 3 showed extreme negative values in all three tests, Tajima's D, Fu & Li D* and F*, ≤ - 2. A large majority of the erythrocyte receptor and merozoite genes have a negative Tajima's D even when compared with previously published whole genome data. Thus, highlighting EBA175 region II and MSP1-33, as outlier genes with a positive Tajima's D (>1). Both these genes contain multiple polymorphisms, which in the case of EBA175 may counteract receptor polymorphisms and/or evade host immune responses and in MSP1 the polymorphisms may primarily evade host immune responses.